Dynamic Thermal Analysis of Machines in Running State - Wang, Lihui (Springer London : Imprint: Springer, 2014)
With the increasing complexity and dynamism in today's machine design and development, more precise, robust and practical approaches and systems are needed to support machine design. Existing design methods treat the targeted machine as stationery. Analysis and simulation are mostly performed at the component level. Although there are some computer-aided engineering tools capable of motion analysis and vibration simulation etc., the machine itself is in the dry-run state. For effective machine design, understanding its thermal behaviours is crucial in achieving the desired performance in real situation. Dynamic Thermal Analysis of Machines in Running State presents a set of innovative solutions to dynamic thermal analysis of machines when they are put under actual working conditions. The objective is to better understand the thermal behaviours of a machine in real situation while at the design stage. The book has two major sections, with the first section presenting a broad-based review of the key areas of research in dynamic thermal analysis and simulation, and the second section presents an in-depth treatment of relevant methodology and algorithms, leading to better understanding of a machine in real situation. The book is a collection of novel ideas, taking into account the need for presenting intellectual challenges while appealing to a broad readership, including academic researchers, practicing engineers and managers, and graduate students. Given the essential role of modern machines in factory automation and quality assurance, a book dedicated to the topic of dynamic thermal analysis, and its practical applications to machine design would be beneficial to readers of all design and manufacturing sectors, from machine design to automotive engineering, in better understanding the present challenges and solutions, as well as future research directions in this important area.